The effects of isolated single umbilical artery on first and second trimester aneuploidy screening test parameters. (April 2015) - Tulek, Firat; Kahraman, Alper; Taskin, Salih; Ozkavukcu, Esra; Soylemez, Feride
Abstract Objective: Reliability of first and second trimester screening tests largely depends on accurate estimation of maternal serum marker values. Reduced reliability could lead redundant invasive tests or misdiagnosis. Adjustments of serum marker values for confounding factors like insulin-dependent diabetes, maternal weight or maternal rhesus status are essential. We aimed to investigate whether isolated single umbilical artery alters first and second trimester test parameters or not. Methods: Routine detailed obstetric ultrasonographies performed were retrospectively screened for this study. Among spontaneously conceived singleton pregnancies, women who were found to have single umbilical artery without any additional structural anomalies or aneuploidies were selected. First and second trimester screening test results were accessible for 98 and 102 of the cases with isolated single umbilical artery, respectively. Results: Among first trimester screening test parameters, PAPP-A (pregnancy-associated plasma protein A) MoMs were found significantly higher in isolated single umbilical artery group. AFP MoMs were found significantly elevated in isolated single umbilical artery group in second trimester quadruple tests. Conclusion: Existence of single umbilical artery could alter the estimation of MoM values of maternal serum markers. Reliability of prenatal screening tests could be improved by adjusting these parameters in accordance with isolated single umbilical artery.